An uneven path to accountability: a comparative study of MGNREGA in two states of India - Dutta, Sujoy (Discussion Papers / Wissenschaftszentrum Berlin für Sozialforschung, Forschungsschwerpunkt Bildung, Arbeit und Lebenschancen, Abteilung Ungleichheit und soziale Integration, 2015)
In India, a lack of accountability is considered the key reason for the failure of most development programs. Most poverty alleviation programs are riddled with inefficiency, absenteeism, incompetence, and corruption. This has resulted in poor service delivery, and to ordinary citizens losing trust. This paper examines whether Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) is accountable to ordinary citizens, and civil society's role in making the Act viable. This study draws upon empirical evidence from two states of India - Andhra Pradesh (AP) and Uttar Pradesh (UP). The findings suggest that this Act has been implemented relatively well in AP, despite the state's dismal performance in the implementation of most welfare programs. The political class in AP has taken a keen interest in the Act, rather than in using it to amass wealth for their political activities. Social audits have been institutionalized with the help of civil society organisations, providing a